1982
DOI: 10.1126/science.7100916
|View full text |Cite
|
Sign up to set email alerts
|

Diving Depths and Energy Requirements of King Penguins

Abstract: During 4- to 8-day periods at sea, half of 2595 dives of three king penguins were more than 50 meters and two dives exceeded 240 meters. The at-sea metabolic rate, estimated from the turnover of tritiated water, was 2.8 times the standard metabolic rate and requires about 2.5 kilograms of squid per day. Ten percent or less of the dives may result in prey capture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(55 citation statements)
references
References 9 publications
0
54
1
Order By: Relevance
“…Therefore, the total energetic cost for both onshore and at-sea components is (1 1.9 W x 0.493) + (27.8 W x 0.507) = 20.0 W, which is 1.76 times the predicted BMR (Ellis 1984). This value is significantly lower than comparable values of 2.8 for King Penguins Aptenodytes patagonicus (Kooyman et al 1982), 2.6 and 2.9 for Gentoo Pygoscelis papua and Macaroni Eudyptes chrysolophus Penguins (Davis et al 1983); 2.2 for Little Penguins ) and 2.6 for Jackass Penguins . Extensive studies of hirundines, for which flight costs are a significant portion of field metabolism, have yielded values between 2.2 and 5.3 (Hails & Bryant 1979).…”
Section: Metabolic Ratementioning
confidence: 49%
See 1 more Smart Citation
“…Therefore, the total energetic cost for both onshore and at-sea components is (1 1.9 W x 0.493) + (27.8 W x 0.507) = 20.0 W, which is 1.76 times the predicted BMR (Ellis 1984). This value is significantly lower than comparable values of 2.8 for King Penguins Aptenodytes patagonicus (Kooyman et al 1982), 2.6 and 2.9 for Gentoo Pygoscelis papua and Macaroni Eudyptes chrysolophus Penguins (Davis et al 1983); 2.2 for Little Penguins ) and 2.6 for Jackass Penguins . Extensive studies of hirundines, for which flight costs are a significant portion of field metabolism, have yielded values between 2.2 and 5.3 (Hails & Bryant 1979).…”
Section: Metabolic Ratementioning
confidence: 49%
“…T h e implications of sea-water ingestion are treated in the discussion. Similar estimates of prey intake in penguins via water influx measurements gave realistic rates of food ingestion and it is unlikely that significant sea-water ingestion occurred (Kooyman et al 1982, Davis et al 1983. Furthermore, validation studies on pinnipeds indicate excellent agreement between actual food intake and food intake estimated from water influx measurements (differences of -2.3 yo in Northern Fur Seals Callorhinus ursinus (Costa & Gentry 1986) and 1 and 10% in California Sea Lions Zalophus californianus (Costa 1984).…”
Section: Food Intakementioning
confidence: 66%
“…Despite its limitations, this first recording system for seabirds at sea revealed penguins to be able to dive to depths that far exceeded previous thinking, and demonstrated that these birds must have remarkable physiological mechanisms allowing them to withstand very high pressures and to breath-hold for the presumed extended periods of time necessary to reach those depths (Kooyman 1975, Kooyman et al 1982. The 'dusted capillary tube depth gauge' was so small, robust and cheap that it could be deployed on a large range of diving seabird species and, over time, this instrument was applied on other, much smaller, species.…”
Section: In-depth View Of Seabird Foragingmentioning
confidence: 99%
“…The interface between old-style data re cording and the more sophisticated solid-state devices which recorded parameters as a proper function of time was a multiple maximum depth recorder, first used by Kooyman et al (1982). This unit simply recorded the number of dives made by a bird that exceeded a certain depth threshold.…”
Section: Interface With Electronicsmentioning
confidence: 99%
See 1 more Smart Citation